Geological controls for gas hydrates and unconventionals - Rajput, Sanjeev; Thakur, Naresh Kumar (Elsevier, 2016)
Geological Controls for Gas Hydrate Formations and Unconventionals tells the story of unconventional hydrocarbon resources, especially gas hydrates, tight gas, shale gas, liquid- rich shale, and shale oil, to future generations. It presents the most current research in unconventionals, covering structural constituents of continental margins and their role in generating hydrocarbons.iA Additionally, this book answers basic questions regarding quantifications and characterizations, distributions, modes of occurrence, physical and chemical properties, and more - in essence, all the information that is necessary to improve the models for precision prediction of the enigma of gas hydrates and other unconventionals. Blending geology, geophysics, geomechanics, petrophysics, and reservoir engineering, it explains in simple language the scientific concepts that are necessary to develop geological and reservoir models for unconventionals. Serving as a focal point for geoscientists and engineers conducting research that focuses on reservoir characteristics of unconventionals, Geological Controls for Gas Hydrate Formations and Unconventionals is a useful resource for a variety of other specialiststies including physicists, geochemists, exploration geologists, and petroleum and reservoir engineers. It details the key factors for successful exploration and development of unconventional reservoirs including discovery, data evaluation, full-field development, production, and abandonment, along with a vivid description ofn the worldwide occurrence of unconventional hydrocarbons.